Potensi Ekstrak Etanol Daun Sirih (Piper Betle L.) Sebagai Pengganti ADP (Adenosine Diphosphate) Pada Pemeriksaan Agregasi Trombosit - Andri Sukeksi; Rizqi Yogania Rahmawati (Lontara Journal of Health Science and Technology, 2021)
Adenosine diphosphate (ADP) reagent is often used in the examination of platelet aggregation, yet has limitations in terms of price and availability. Natural source namely betel leaf (Piper betle L.) are believed to be used as a substitute for ADP because betel leaf have the characteristics of styptic (to resist bleeding), vulnerary (to heal skin wounds), and anti-inflammatory (to preserve inflammation) (Moeljanto & Mulyono, 2003). The aim of this study was to determine the potential of betel leaf on the examination of platelet aggregation. The method used in this research included the betel leaf extraction using ethanol as solvent with an evaporator. The extract obtained was used as a substitute for the ADP reagent in platelet examination in the form of determining the percentage of platelet aggregation in 16 human blood samples, with a population of students at the University of Muhammadiyah Semarang. The final results showed that the addition of betel leaf extraction to the 16 blood samples examined gave an average value of platelet aggregation percentage which was higher (65%) than the mean value of platelet aggregation using ADP reagent mixing (57%). Both results fall within the normal value range, namely 50-70%. It can be concluded that betel leaf extract has the potential to be used as a replacement reagent for ADP in the process of examining platelets, especially in determining the percentage value of platelet aggregation.